Transforming Supply Chain Management through Modern B2B Data Integration - Pramod Kumar Muthyala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the evolution and current state of B2B integration in supply chain management, focusing on implementation challenges, success factors, and future trends. The article examines case studies from industry leaders, including 3M and Advance Auto Parts, demonstrating how modern B2B integration platforms have transformed traditional supply chain operations through automated data exchange, improved visibility, and enhanced collaboration. The article investigates technical and organizational challenges in implementation while providing best practices for successful deployment. The article offers insights into the future direction of B2B integration technologies and their impact on business performance through detailed analysis of cloud computing, API-first approaches, and artificial intelligence applications.